2017
DOI: 10.1038/labinvest.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Immune microenvironment of gliomas

Abstract: High-grade gliomas are rapidly progressing tumors of the central nervous system (CNS) with a very poor prognosis despite extensive resection combined with radiation and/or chemotherapy. Histopathological and flow cytometry analyses of human and rodent experimental gliomas revealed heterogeneity of a tumor and its niche, composed of reactive astrocytes, endothelial cells, and numerous immune cells. Infiltrating immune cells consist of CNS resident (microglia) and peripheral macrophages, granulocytes, myeloid-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
459
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(471 citation statements)
references
References 237 publications
(282 reference statements)
7
459
3
2
Order By: Relevance
“…Glioma cells could release multiple cytokines that promote the infiltration of various immune cells such as MDSCs, microglia, Tregs, macrophages, CD8 T cells, and CD4 T cells into the tumor microenvironment, as tumors not only recruit immune cells, but also transform said cells into phenotypes that can help tumor cells evade immune system surveillance (Table ). For example, Roesch et al reported that macrophages/glioma‐associated microglia (GAMs) tend to gather in tumor sites and generate an immunosuppressive tumor microenvironment which promote glioma invasion, growth, and angiogenesis . Interestingly, one novel discovery of the present study is that COPB2 was involved in the immune microenvironment of glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioma cells could release multiple cytokines that promote the infiltration of various immune cells such as MDSCs, microglia, Tregs, macrophages, CD8 T cells, and CD4 T cells into the tumor microenvironment, as tumors not only recruit immune cells, but also transform said cells into phenotypes that can help tumor cells evade immune system surveillance (Table ). For example, Roesch et al reported that macrophages/glioma‐associated microglia (GAMs) tend to gather in tumor sites and generate an immunosuppressive tumor microenvironment which promote glioma invasion, growth, and angiogenesis . Interestingly, one novel discovery of the present study is that COPB2 was involved in the immune microenvironment of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma cells could release multiple cytokines that promote the infiltration of various immune cells such as MDSCs, microglia, Tregs, macrophages, CD8 T cells, and CD4 T cells into the tumor microenvironment, 22 as tumors not only recruit immune cells, but also transform said cells into phenotypes that can help tumor cells evade immune system surveillance ( In recent years, the use of immune checkpoint inhibitors (ICIs) has been popular in the treatment of malignant tumors. 25,26 Some ICIs, such as anti-PD-1 antibody, are superior to traditional chemoradiotherapy in terms of its clinical curative effect.…”
Section: Discussionmentioning
confidence: 99%
“…6 Unlike classically activated M1 macrophages, which are characterized by their promotion of an antitumor response, TAMs have an immunosuppressive role, thus being defined as the alternatively activated M2 phenotype. [7][8][9] TAMs promote glioma progression through secretion of TGFβ1, IL-6, VEGF, PDGF, periostin, MMP2, and MMP9, maintaining the phenotype of glioma stem-like cells, promoting angiogenesis, and regulating degradation of the extracellular matrix (ECM), thus leading to glioma growth, invasion, and the formation of distant pre-metastatic niches. 10,11 Moreover, the immunosuppressive microenvironment induced by TAMs suppresses the systemic immune response by blocking T-cell proliferation, increasing T-cell apoptosis, inhibiting cytotoxic T lymphocyte (CTL) response, and promoting other immunosuppressive cells such as MDSCs and Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…Only upon CNS injury do some of these cellular barriers become fenestrated to allow for immune cell entrance. Although microglia are thought to be the main regulator of immune responses within the brain, astrocytes (and other cells) also play key roles in this function [143]. A vast amount of work investigating the astrocyte function in either normal or activated state is often related to the regulation of the immune environment in the CNS, as shown in functional studies and astrocyte secretome studies, summarized well by Sofroniew et al [144][145][146][147].…”
Section: Astrocytes As An Immune Regulator In the Tumor Microenvironmentmentioning
confidence: 99%